2016
DOI: 10.5114/ceji.2016.63122
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole therapy in children with frequently relapsing and steroid-dependent nephrotic syndrome: a single-center experience

Abstract: IntroductionNumerous studies suggest that levamisole, an antihelmintic agent with an immunomodulatory effect, reduces the number of relapses in children with frequently relapsing and steroid-dependent nephrotic syndrome (FRNS/SDNS). The aim of the study was to present a single center’s experience in treatment of FRNS and SDNS with levamisole.Material and methodsAmong 72 children with FRNS/SDNS treated in our department with levamisole in the years 1984-2011 we studied in detail 53 patients (mean age: 6.5 ±3.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“… 23 We also did not find significant adverse effects suggesting safety of drug as observed by others. 20 - 24 Considering the results of Sinha A et al in above RCT, Vivarelli M et al also suggested use levamisole in FR/SD. 25 Levamisole is also under investigation as adjuvant agent after induction of remission with daily dose in children during first episode of nephrotic syndrome to prevent future relapses and morbidity associated with long term steroid therapy.…”
Section: Discussionmentioning
confidence: 97%
“… 23 We also did not find significant adverse effects suggesting safety of drug as observed by others. 20 - 24 Considering the results of Sinha A et al in above RCT, Vivarelli M et al also suggested use levamisole in FR/SD. 25 Levamisole is also under investigation as adjuvant agent after induction of remission with daily dose in children during first episode of nephrotic syndrome to prevent future relapses and morbidity associated with long term steroid therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Levamisole is a promising steroid-sparing agent since it has relatively few side effects compared with other steroid-sparing drugs. This has been shown in several RCTs in children with FRNS and SDNS 6–8 12 34–37. Its mode of action is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these RCTs, there have been a lot of smaller retrospective studies in the last decade, but most often only single center experiences have been published [35,36,37,38,39,40]. These papers stated that in children with FRNS or SDNS [36,37,38,40], levamisole could be effective in decreasing relapse risk and frequency. However, some of these studies used low-dose prednisolone or a slowly tapering regimen in addition to 2–2.5 mg/kg body weight levamisole on alternate days [27].…”
Section: The Use Of Levamisole In the Treatment Of Nephrotic Syndromementioning
confidence: 99%
“…Single cases of gastrointestinal disturbances [31,41] or leukopenia [25,31] have been reported in the RCTs, probably caused by the use of levamisole. Most retrospective studies reported no side effects of levamisole [37,39,40], or only minor reversible effects such as rash, fever, abdominal pain, elevated liver enzymes, neutropenia or thrombocytopenia, which all disappeared after cessation of levamisole [36,52]. In their placebo-controlled multi-centric trial, Gruppen et al showed that the use of levamisole was safe [28].…”
Section: Known Side Effects Of Levamisole Treatmentmentioning
confidence: 99%